Relationship between free fatty acids, insulin resistance markers, and oxidized lipoproteins in myocardial infarction and acute left ventricular failure - Gruzdeva O (Dove Medical Press, 2013)
Olga Gruzdeva, Evgenya Uchasova, Yulia Dyleva, Ekaterina Belik, Vasily Kashtalap, Olga BarbarashFederal State Budgetary Institution Research Institute for Complex Issues of Cardiovascular Diseases, Kemerovo, RussiaBackground: The most common cause of myocardial infarction (MI) is stenotic atherosclerotic lesions in subepicardial coronary arteries. Artery disease progression induces clinical signs and symptoms, among which MI is the leader in mortality and morbidity. Recent studies have been trying to find new biochemical markers that could predict the evolution of clinical complications; among those markers, free fatty acids (FFA) and oxidative modification of low-density lipoproteins (oxidized LDL) have a special place.Materials and methods: Seventy-nine ST-elevation MI patients were enrolled. The first group included MI patients without the signs of acute heart failure (Killip class I) while MI patients with Killip classes II–IV made up the second group. Thirty-three individuals with no cardiovascular disease were the controls. The lipid profile, serum oxidized LDL, and their antibodies, C-peptide and insulin were measured at days 1 and 12. The level of insulin resistance was assessed with the quantitative insulin sensitivity check index (QUICKI).Results: MI patients had atherogenic dyslipidemia; however, the Killip II–IV group had the most pronounced and prolonged increase in FFA, oxidized LDL, and their antibodies. Additionally, positive correlations between FFA levels and creatine kinase activity (12 days, R = 0.301; P = 0.001) and negative correlations between the QUICKI index and FFA levels (R = –0.46; P = 0.0013 and R = –0.5; P = 0.01) were observed in the both groups.Conclusion: The development of MI complications is accompanied by a significant increase in FFA levels, which not only demonstrate myocardial injury, but also take part in development of insulin resistance. Measuring FFA levels can have a great prognostic potential for risk stratification of both acute and recurrent coronary events and choice of treatment strategy.Keywords: myocardial infarction, free fatty acids, insulin resistance